KORELASI KECEMASAN DAN DOMAIN KELELAHAN PADA PASIEN TUBERKULOSIS - Tasnim Tasnim; Ferdy Lainsamputty (Fakultas Keperawatan, Universitas Klabat, 2021)
Tuberculosis (TB) is a major health problem in many countries worldwide, ranked at the same level as Human Immunodeficiency Virus (HIV). In patients with TB, anxiety comes from the worsening of disease that created feeling of distress and fatigue. This study aimed to examine the relationship between anxiety and fatigue domains among tuberculosis patients. This study used a descriptive correlation design with cross-sectional approach. Consecutive sampling technique was used to recruit 70 participants from a general hospital in Central Sulawesi Province, Indonesia. The questionnaires used were Hamilton Anxiety Rating Scale (HAM-A) and Multidimensional Assessment of fatigue (MAF). Descriptive statistics and Spearman Correlation used to examine the relationship between variables. Anxiety had a significant correlation with distress domain of fatigue (r = 0,24, p < 0,05). Those who experienced greater anxiety suffered more mental fatigue. Tuberkulosis (TB) merupakan masalah kesehatan utama di berbagai negara di dunia, berada diperingkat sama dengan penyakit HIV yang mematikan. Kecemasan pada pasien TB bersumber dari progress memburuknya penyakit sehingga membuat pasien tertekan secara psikologis dan mengalami kelelahan. Penelitian ini bertujuan untuk mengetahui hubungan kecemasan dan domain kelelahan pada pasien tuberkulosis. Penelitian ini berjenis deskriptif korelasi dengan pendekatan potong lintang menggunakan 70 sampel, yang direkrut dengan teknik consecutive sampling dari salah satu rumah sakit umum daerah di Sulawesi Tengah. Kuesioner yang digunakan yaitu Hamilton Anxiety Rating Scale (HAM-A) dan Multidimensional Assessment of Fatigue (MAF). Statistik deskriptif dan korelasi Spearman digunakan untuk mencari hubungan antar variabel. Kecemasan memiiki korelasi yang siginifikan dengan domain tekanan kelelahan (r = 0,24, p < 0,05). Partisipan dengan kecemasan berat, menderita kelelahan mental yang lebih parah.